1996
DOI: 10.1002/(sici)1098-1004(1996)7:3<202::aid-humu4>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Database of mutations in the p53 and APC tumor suppressor genes designed to facilitate molecular epidemiological analyses

Abstract: Germline and somatic mutations in the p53 and APC genes contribute to neoplasia. The patterns of these and other acquired mutations in cancers reflect environmental mutagens and endogenous factors that contribute to carcinogenesis. Herein, we describe a database of almost 2,300 mutations in the p53 and APC genes published until September 1, 1993. In addition to cataloging the mutations, multiple fields of information have been added to facilitate future molecular epidemiological analyses of human cancer. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, 30% of TP53 mutations would have been missed in studies focusing only to exons 5-8 of the TP53 gene. Other studies have also shown that a considerable fraction of protein truncating mutations occurs outside the evolutionary conserved region of TP53 [3,28].…”
Section: Survival Comparisons By Tp53 Mutation Typementioning
confidence: 99%
“…Thus, 30% of TP53 mutations would have been missed in studies focusing only to exons 5-8 of the TP53 gene. Other studies have also shown that a considerable fraction of protein truncating mutations occurs outside the evolutionary conserved region of TP53 [3,28].…”
Section: Survival Comparisons By Tp53 Mutation Typementioning
confidence: 99%
“…Mutations of p53 in the indicated xenograft lines were determined by Sanger sequencing of cDNA generated by reverse transcription polymerase chain reaction. R175C is a known mutation in colon and uterine cancer [1] that has been reported to retain wild-type functions [2]. R273C is a known mutation in multiple cancers [1].…”
Section: Supp Tablementioning
confidence: 99%
“…R175C is a known mutation in colon and uterine cancer [1] that has been reported to retain wild-type functions [2]. R273C is a known mutation in multiple cancers [1]. N239 insertion is a novel mutation in the DNA binding domain of p53.…”
Section: Supp Tablementioning
confidence: 99%